The study of the prevalence and impact of polymorphism of the C/Т gene ACTN3 (RS1815739) in the physical development of children born with low birth weight - Levchuk-Vorontsova, T. O. (Journal of Education, Health and Sport, 2020)
The work aims at studying the prevalence and influence of polymorphism of the C/T gene polymorphism of ACTN3 gene (rs1815739) on the physical development of children born with low body weight. Materials and methods of research. To study the C/T polymorphism of the ACTN3 gene (rs1815739), 170 newborns were examined. Newborns were divided into 4 groups depending on birth weight: Group I - 50 premature babies weighing 1500-1999 grams (1776.26 ±20.06 grams), Group II - 64 premature babies with birth weight 2000-2499 grams (2225.31±19.46 grams), group III - 25 children with normal gestational age at birth, but with intrauterine growth retardation (2105.00±56,41), group IV (control group) - 31 children with normal gestational age and birth weight more than2500 grams (3009.03±73.04 grams). Genotyping was performed by polymerase chain reaction according to the instructions (Applied Biosystems, USA) using total DNA samples isolated from whole venous blood using a set of reagents "SNP-Screen" (manufactured by "Syntol") on the CFXteTM Real-Time PCR amplifier (Bio-Rad Laboratories, Inc., USA). Results. In all studied children, the frequency of detection of C allele polymorphism of the C / T gene polymorphism of the ACTN3 gene (rs1815739) was 51.47%, T allele - 48.52%., The frequency of genotypes had the following distribution: CC-30.59%, TT- 26.65%, CT-41.76%. In this case, in group I was the following distribution of alleles and genotypes: alleles C and T were detected in the ratio of 46.67% to 53.93%, genotypes SS-32.00%, TT-28.00%, ST-40, 00%, in group II alleles - C-51,56%, T - 48,44%, genotypes - СС 28,13%, TT-25,00%, СT - 46,88%, in group III - allele C was significantly more often registered than T (68.00% vs. 32.00%, p <0.05) and genotype TT - more often than CC and CT (52.00% vs. 16.00% and 32.00%). In IV (control) group there was the following distribution of the frequency of alleles and genotypes of gene polymorphism: allele C - 40.00%, allele T - 60.00%, genotype CC - 38.71%, genotype TT - 19.35%, genotype CT -41.93%. The lowest monthly values of body weight and weight gain were associated with the TT genotype of the ACTN3 gene (rs1815739) in preterm infants and children with normal gestational age at birth, but with intrauterine growth retardation in the first half, and among children in the comparison group - in the second half, but the overall weight gain for 12 months had no genotypic dependence. Premature infants (observation groups I and II) with the TT genotype of the ACTN3 gene (rs1815739) had unevenly lower body lengths during the first year of life, while children with normal gestational age at birth, but with intrauterine growth retardation lagged behind in their growth in the first year, and children from the control group - in the second half. The total annual increase in body length for the first year of life in all children with the TT genotype was the lowest and amounted to in the first group - 28.50 ±1.03 cm, in the second - 24.03 ±0.93 cm, in the third - 25.50 ±1.04 cm, in IV - 23.00 ±0.98 cm. A probable positive correlation was found between the duration of breastfeeding and the monthly increase in body length in children with the TT genotype of the ACTN3 gene (rs1815739): γ = 0.58, γ = 0.76, γ = 0.61 from the I, II and III observation groups, respectively. Conclusions. It was found that the TT genotype of the ACTN3 gene (rs1815739) in children is associated with their uneven physical development in the first year of life and significantly lower rates of body length gain in 12 months, and long-term breastfeeding, especially premature babies and children with delayed fetal development, their normal growth.